INCREASING ELDERLY KNOWLEDGE ABOUT NON-COMMUNICABLE DISEASES IN POLENGAN VILLAGE, MAGELANG DISTRICT - Nur Fitri Ayu Pertiwi; Helmi Nurlaili (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2023)
This research was motivated by the need for education regarding non-communicable diseases that occur in the elderly in Polengan Village, Magelang Regency. This research is the first research conducted to assess changes in elderly knowledge regarding non-communicable diseases that often occur in the elderly. A total of 25 subjects participated in this study (n = 25; 18 women, 7 men). Data were collected using a questionnaire regarding non-communicable diseases that occur in the elderly. The results of the questionnaire showed an increase in poor knowledge by 44%, good 32%, and very good 24%. After providing education regarding non-communicable diseases, knowledge increased to less than 0%, sufficient to 24%, and good to 76%. The results of this research show a good change in knowledge after being given counseling. Keywords : Elderly, Non-Communicable Diseases.